Frozen [videorecording (DVD)] - Buck, Chris; Bell, Kristen, 1980-; Gad, Josh, 1981-; Menzel, Idina (Walt Disney Studios Home Entertainment, 2014)
When a prophecy traps a kingdom in eternal winter, Anna, a fearless optimist, teams up with extreme mountain man Kristoff and his sidekick reindeer Sven on an epic journey to find Anna's sister Elsa, the Snow Queen, and put an end to her icy spell. Encountering mystical trolls, a funny snowman named Olaf, Everest-like extremes and magic at every turn, Anna and Kristoff battle the elements in a race to save the kingdom from destruction.